IMPLEMENTASI KEGIATAN EKSTRAKURIKULER DALAM MENANAMKAN KARAKTER RELIGIUS DI MADRASAH TSANAWIYAH DARUL AMANAH DESA PANDAHAN KECAMATAN BATI-BATI - Asep Saefuloh; Imaniah Elfa Rachmah; Muhamad Ramli (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2020)
This research discusses the implementation of extracurricular activities in instilling religious character in Madrasah Tsanawiyah Darul Amanah Pandahan Village, Bati-Bati District. The purpose of this study was to determine the implementation of extracurricular activities in instilling religious character in Madrasah Tsanawiyah Darul Amanah Pandahan Village, Bati-Bati District and the supporting and inhibiting factors that influence these activities. In extracting data, researchers used observation, interview, and documentation techniques. Data management techniques are done by editing, data classification, and data interpretation. Then analyzed with qualitative descriptive analysis and inductive conclusions drawn. Based on the results of the study, it is known that the implementation of extracurricular activities in Madrasah Tsanawiyah Darul Amanah has been going well. The implementation of extracurricular activities is influenced by supporting factors, namely educational background factors and the personality of teachers who teach in these extracurricular activities as well as the Islamic community environment so that the implementation of extracurricular activities in inculcating religious character can run well.